Alcohol use disorder and use of rhythm control therapies in patients with atrial fibrillation: A nationwide cohort study - Vanhanen, Miika; Jaakkola, Jussi; Airaksinen, Juhani K.E.; Halminen, Olli; Putaala, Jukka; Mustonen, Pirjo; Haukka, Jari; Hartikainen, Juha; Luojus, Alex; Niemi, Mikko; Linna, Miika; Lehto, Mika; et al. (Elsevier BV, 2026)
Objective:
Patients with alcohol use disorder (AUD) often receive inferior treatment for somatic comorbidities. We aimed to examine whether AUD is associated with disparities in the use of antiarrhythmic therapies (AAT) for rhythm control in atrial fibrillation (AF) patients, using a nationwide registry.
Methods:
The Finnish AntiCoagulation in Atrial Fibrillation (FinACAF) registry includes all 229,565 patients with incident AF diagnosed in Finland between 2007 and 2018, identified from comprehensive national healthcare registries. The primary outcome was initiation of rhythm control therapies, including antiarrhythmic drugs, cardioversion, and catheter ablation, in patients with and without AUD.
Results:
The mean age was 72.7 years, 50 % were female and 4.7 % had AUD. Rhythm control was initiated less often in patients with AUD compared to those without (13.6 % vs. 21.8 %, p < 0.001). After adjustment for comorbidities and socioeconomic status, AUD remained associated with lower use of rhythm control therapies (HR 0.65; 95 % CI 0.62–0.69). This disparity was consistent across all modalities of rhythm control (antiarrhythmic drugs, cardioversion and catheter ablation). While no significant interaction was observed with sex or age, income modified the association (p < 0.001), with the lowest income tertile showing the greatest disparity (HR 0.37; 95 % CI 0.32–0.42).
Conclusions:
AUD is independently associated with markedly lower use of rhythm control therapies in AF patients. These disparities are most pronounced among socioeconomically disadvantaged individuals, highlighting the need for targeted interventions to ensure equitable treatment access.